Language issues in Sri Lanka: an analysis from linguistic and Islamic perspectives - Abdul Rauff, Mohamed Mahsoom; Mohamed Mahroof, Ali Abdullah; Abd Rahman, Akmal Khuzairy (Faculty of Islamic Studies Wiralodra University, 2025)
The study aims to analyze linguistic issues through the linguistic and Sharia aspect in a pluralistic environment, based on the prevailing conditions in Sri Lanka. The study stressed that the multilingual Sri Lankan environment necessitates the dignity, freedom, equality and identity that the United Nations has nominated for the preservation of human rights and which itself has been affirmed by the lofty guidelines of Islamic legislation for building a nation with united individuals and a strong foundation. In addition, achieving this potentialdepends on cultural awareness and general understanding on the part of citizens, which results in obtaining convincing solutions to many conflicts that arise from linguistic issues. Perhaps this study helps decision-makers and social activists to recognize linguistic and cultural versatility and consider it while addressing linguistic issues in a context in which languages and races are diverse.